The role of performance pressure during shootouts in soccer - Van Hemert, R.; Van Der Kamp, J. (International Journal of Sport Psychology, 2025)
This study aimed to investigate multiple situational and individual constraints as stressors during penalty kick shootouts in professional soccer. To this end, we replicated and extended previous studies by Jordet et al. (2007), Jordet and Hartman (2008), and Jordet (2009). The constraints previously identified to predict the outcome of penalty kicks were revisited to confirm that the earlier findings still hold. The extension was twofold; 1) a three times larger dataset was used, and 2) all potential predictors and covariates included in the former three studies were analysed in one encompassing binary logistic regression. The results showed that tournament level, kick round, and kick valence significantly predicted kick outcome, although the full model only had limited predictive power. In contrast to Jordet (2009), there was no support that high public status predicted performance. Overall, the current study largely supports earlier observations and interpretations that situational constraints via appraisal and coping influence performance pressure, which influences players` performance during shootouts.